Complete mitogenome and phylogenetic analysis of the tropical rocky shore crab Grapsus albolineatus (Lamarck, 1818) (Crustacea: Grapsoidea). Issue 11 (2nd November 2022) - Wang, Xiyue; Xu, Shuyi; Chen, Wenwen; Hu, Xintong; Cui, Lingxue; Li, Xue; Qu, Jiangyong; Wang, Xumin; Wang, Lijun
Abstract: In this study, the complete mitogenome of Grapsus albolineatus (Lamarck, 1818) (Crustacea: Grapsoidea) was sequenced. The mitogenome of G. albolineatus was a circular molecule with 15, 578 bp length. Its nucleotide composition was 26.81% A, 16.37% G, 34.51% T, and 22.31% C. It comprised 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA), and two ribosomal RNA (rRNA). All PCGs were initiated by ATN codons, except for the atp8 and nad1 genes. Ten PCGs used a common stop codon of TAA or TAG, and the other three ended with a truncated stop codon (a single stop nucleotide T). Phylogenetic analysis revealed that G. albolineatus was closely related to species from the genera Pachygrapsus and Metopograpsus .